Subtexts of Most Read Articles on Social Sciences Citation Index: Trends in Educational Issues - Köybaşı Şemin Fatma (De Gruyter, 2024)
Although education is mostly the duty of educators, it is an important field that concerns all segments of society. Studies and regulations on education on a global scale have gained momentum in terms of increasing both quality and quantity. Which issues related to education are considered important and which problems are focused on can be a guide in giving direction to the regulations in education. In this study, a total of 351 articles published in SSCI journals are reviewed, with documentary analysis, and the subject areas of the most read articles on education are discussed. The most-read articles on education focus on the themes of inequality and injustice in critical education. Other results of the research are discussed in detail in the article.